Evaluation of the effect of statin treatment on intracranial atherosclerotic plaques using magnetic resonance vessel wall imaging: a case series - Yang, Ke; Zhou, Pengyu; Wang, Yuting; Huang, Bin (Frontiers in Neurology, 2025)
IntroductionIntracranial artery stenosis highly increases the recurrence risk of transient ischemic attack and ischemic stroke, especially in Chinese patients. Patients with intracranial atherrotic disease (ICAD) should be actively treated with risk factor control, such as lipid management. This report discusses vessel wall MRI (VW-MRI) to evaluate plaque in-situ changes in four patients with ICAD after anti-lipid therapy of statins.Case reportFour patients with ischemic stroke and ICAD were prospectively enrolled. VW-MRI and serum low-density lipoprotein cholesterol (LDL-C) were assessed at baseline and follow-up (at least 11–12 months). All patients received statins throughout the study. Compared with baseline, the LDL-C decreased in one case, the length of basilar artery plaque and the overall plaque enhancement segment were shortened, and the plaque thickness was reduced, indicating that the plaque tended to regress. In the second case, LDL-C increased after one year compared with baseline, along with upgraded plaque enhancement and new intraplaque hemorrhage, indicating plaque progression. After 2.5 years, LDL-C decreased significantly, while VW-MRI changes were minimal. LDL-C increased in the third case, but VW-MRI indicated plaque regression. In the fourth case, LDL-C decreased significantly, and the degree of basilar artery plaque stenosis was reduced. However, plaque enhancement upgraded, and intraplaque hemorrhage increased, indicating plaque progression.ConclusionVW-MRI can monitor the in-situ changes of plaques after lipid-lowering therapy with statins, provide key information that is difficult to reflect in systemic serological lipid indices like LDL-C, and help identify cases that are not responsive to current anti-lipid therapy.